Pengaruh Volume Inokulum Pada Produksi Bioetanol Dari Limbah Kulit Nanas Menggunakan Zymomonas Mobilis Dengan Metode Solid State Fermentation (SSF) - Ikhsan ' Fajrin; Said Zul Amraini; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Increasing of world energy consumption and depleted of availability fossil fuel caused the development of energy goes thru renewable fuel and environment-friendly. Waste of agriculture such as pineapple peel can be utilized as raw material to produce bioethanol through fermentation. The aim of this research  are to know the process of bioethanol production through solid state fermentation (SSF) from pineapple peel and to determine the yield of bioethanol produced using Zymomonas mobilis with various inoculum volume  8, 9, 10, 11, and 12 % and various fermentation time 6, 12, 18, 24, 30 and 36 hours. Fermentation process conducted using Zymomonas mobilis because it has several advantages such as resistant to high concentration of ethanol,more tolerant to temperature and low pH. The result shows that the higher inoculum volume that inoculated to substrate the higher ethanol produced. The highest yield of bioethanol is 21%v at inoculum volume 10%. The optimum fermentation time obtained is 24 hours to all various inoculum volume Keyword : Bioetanol; Fermentasi; Kulit Nanas; Solid State Fermentation (SSF); Zymomonas Mobilis